Short-Term Clinical Outcomes After Anterior Cruciate Ligament Reconstruction In Adolescents During The COVID-19 Pandemic - Adam Weaver; Brandon Ness; Dylan Roman; Nicholas Giampetruzzi; Joshua Cleland (North American Sports Medicine Institute, 2022)
# Background/Purpose The COVID-19 pandemic has impacted adolescents across multiple areas of health. While many factors influence outcomes following anterior cruciate ligament reconstruction (ACLR), the impact of the COVID-19 pandemic on early patient outcomes after ACLR is currently unknown in an adolescent population. The purpose of this study was to determine if short-term clinical outcomes were different in adolescents after ACLR for those who underwent surgery pre-COVID versus during the COVID-19 pandemic timeframe. # Design Retrospective cohort # Methods A retrospective review of records occurred for patients who underwent ACLR with a quadriceps tendon autograft. Two separate review timeframes were defined according to date of surgery (control: September 2017 - October 2019; COVID: March 2020 - May 2021). Patients were classified into pre-COVID (control) and COVID groups by surgical date and were then age- and sex-matched. Three-month postoperative outcomes were included for analysis, including normalized isometric quadriceps and hamstring peak torque, Anterior Cruciate Ligament - Return to Sport after Injury (ACL-RSI), and the Pedi International Knee Documentation Committee Form (Pedi-IKDC) scores. # Results Sixty patients met the inclusion criteria (34 females, 56.7%). Follow-up testing occurred at 3.2 months (98.13 ± 14.91 days) postoperative. A significant difference was found between groups for normalized quadriceps peak torque on the uninvolved limb, with the control group (2.03 ± 0.47 Nm/kg) demonstrating decreased peak torque compared to the COVID group (2.49 ± 0.61 Nm/kg) (p =0.002, effect size (d) = 0.84). For the involved limb, no difference in normalized quadriceps peak torque was observed between the control group (1.25 ± 0.33 Nm/kg) and those who underwent surgery during the COVID-19 pandemic (1.49 ± 0.70 Nm/kg) (p = 0.09). No differences were identified between groups for any of the other strength outcomes (p = 0.31 - 0.87). Similarly, no differences in patient reported outcomes were found for Pedi-IKDC or ACL-RSI between groups (p = 0.12 - 0.43). # Conclusion At roughly three months after ACLR, normalized quadriceps peak torque on the uninvolved limb was reduced by 18.5% for adolescents who underwent surgery pre-COVID versus during the COVID-19 pandemic timeframe. No group differences were observed for other isometric strength outcomes, Pedi-IKDC, or ACL-RSI scores.